Distribution and Characteristics of Water Source in the Prospective Campus Area of UIN Sunan Kalijaga, Pajangan, Bantul - Nurlita, Agessty Ika; Ratnasari, Satiti; Rahayu, Shilfiana; Aisah, Siti (Jurnal Biologi Tropis, 2025)
Water is a fundamental need for human and ecological sustainability. However, rapid land conversion and insufficient conservation efforts pose serious threats to water availability, particularly in karst-dominated areas like Guwosari, Pajangan, and Bantul, where UIN Sunan Kalijaga plans to construct a new campus. This study aims to map and assess the area's distribution and quality of water sources to ensure sustainable use for future campus development. Six water source stations were identified and analyzed for physical (TDS), chemical (pH), and microbiological (E. coli and total coliform) parameters. The findings show that all stations had acceptable TDS and pH levels for domestic use. Yet, none met the microbiological standards for hygiene and sanitation, as total coliform and E. coli levels exceeded permissible limits. Vegetation analysis revealed the presence of key water-retaining species, such as coconut, bamboo, teak, mahogany, and Ficus septica, which play crucial ecological roles in groundwater conservation. The study highlights the importance of water quality monitoring and vegetation management in campus infrastructure planning. Effective water treatment strategies are recommended to improve microbial quality before human consumption or domestic application.